microRNAs – endogenous regulators of expression of genes participating in the formation of the animals productivity (Eurasian Journal of Ecology, 2018)
We investigated the binding of miRNAs to the mRNAs genes encodingcertain proteins of milk with a view to establishing the degree of the corresponding gene expression regulation. Also it was found out that the influence of miRNAs gene expression of transcription factors, the most largefamily ZNF, including those that affect the transcription of genes involvedin the formation of milk quality. It is found that the mRNA encoding thegrowth hormone gene (GH1) and beta-lactoglobulin (LGB) can bind withhigh affinity to multiple miRNAs. miRNAs binding sites were located inthe 3’UTR and CDS of GH1 gene mRNA and 3’UTR of LGB gene mRNA.The targets of miRNAs genes were CEBPB, EIF5, MLXIPL, NF1, POU2F1,SP1 and STAT5, which involved in the formation of protein, carbohydrateand lipid components of milk. It is shown that miR-3960 has two regionwith multiple binding sites with the value of ∆G/∆Gm from 92 to 98% inthe SEVRV gene mRNA. These sites are located in the CDS and encodedoligopeptides RRRRRRRR or AAAAAAA. Multiple binding sites (nine) formiR-466 were detected in SP1 gene mRNA with ∆G/∆Gm value from 89 to91%. mRNA of MLXIPL gene served as a target of miR-466, miR-3130-3p,miR-3926, miR-4685-5p, miR-5196-5p and miR-6760-5p, which showthe dependence of MLXIPL protein synthesis from many factors. The expression of the POU2F1 gene depended on miR-566, miR-1273d, miR-1273rd and miR-4295. On the mRNAof NF1 and STAT5A genes influencedby three miRNAs and the other genes are targets for one miRNA each.Multiple miR-466 binding sites were found in mRNA of DCL11B, EGR3,MECOM, PRDM1 and ZSCAN12 genes, for miR-574 – in mRNA of KLF7,SNAI2, ZEP91 and ZNF6772 genes, for miR-3960 – in mRNA of KLF4,ZEP91 ZIC3, ZNF366, ZNF367 and ZNF827 genes. The obtained datashow a significant effect of miRNAs on the expression of transcription factors genes involved in the formation of protein, carbohydrate and lipidmilk components.